O trabalho de professores de educação especial : análise sobre a profissão docente no estado de São Paulo - Padilha, Adriana Cunha (2012)
This research aims to think about what kind of work conditions teachers of Special Education (SE) from São Paulo State have to confront on their everyday practice. Critical approach was adopted having as methodological proceeding the Collective Analysis of Labor (CAL), which consists on activities of workers analyzing their own work, helped by researchers. The verbal material obtained on the meetings was transcribed, analyzed, grouped and organized, focusing the socially shared collective thinking. Data revealed eight central ideas regarding to stress agents which teachers of Special Education have to handle on their profession: Lack of appreciation of Special Education work; impairments of mental and physical health; low wages; extensive workdays; difficulties related to commuting to work; career plans privileging the merit through evaluation systems; contradictions between different trainings in the area; human relations full of misunderstandings and, last of all, school bureaucracy. The results obtained point that the transformations that occur on working world impair teaching performance of these Special Education professionals through structural instability of work. The research showed that the reorganization of the teaching job with demands for flexibility and competence on work affects the teachers, accompanied by the impasse in teacher training area privileging the medical-psychological model via eased continuing formation courses, being verified a serious imbalance in the forms of attendance at school. The teaching is affected by all these factors, being necessary a greater investment on career as well as the strengthening of trade union representatives as a form of resistance, in search of work as human emancipation synthesis of social relations. It is expected that, thinking about the problem which is being investigated, might support public policies on area and the discussion of teachers category on the struggle for better conditions of work and life.